Base triggered release of insecticide from bentonite reinforced citric acid crosslinked carboxymethyl cellulose hydrogel composites. (20th January 2017) - Sarkar, Dhruba Jyoti; Singh, Anupama
Highlights: Synthesis of citric acid crosslinked CMC hydrogels & their bentonite composite. Hydrogel composites showed pH sensitive water absorbency & viscoelastic properties. Thiamethoxam was loaded in the composites with high encapsulation efficiency. Release of thiamethoxam from composites was enhanced in alkaline pH condition. Abstract: Biopolymeric clay hydrogels composites, synthesized from crosslinking of carboxymethyl cellulose with citric acid in the presence of bentonite, were used to develop base triggered release formulations (TRFs) of thiamethoxam (3-(2-chloro-1, 3-thiazol-5-ylmethyl)-5-methyl-1, 3, 5-oxadiazinan-4-ylidene(nitro)amine) through an ex-situ encapsulation technique. Hydrogels, hydrogel-bentonite composites and their formulations were characterized by 1 H NMR, IR spectroscopy, XRD, and SEM-EDS. Triggered release of thiamethoxam from the developed formulations was studied in water (pH 7–11) with the help of HPLC and subjected to kinetics analysis using different models. The kinetics study showed the release from developed TRFs followed Gallagher–Corrigan equation with an immediate burst release phenomena and higher release rate of thiamethoxam was observed at alkaline pH than neutral condition (pH 7.0). These TRFs of thiamethoxam may be useful for the efficient control of insects which are having alkaline pH in their gut.